U(VI), Np(V), Eu(III) sorption on goethite: A wide-ranging multiradionuclide dataset and uncertainty-aware parametrization of surface complexation models - Romanchuk, Anna Yu.; Svitelman, Valentina S.; Blinov, Peter D.; Larina, Alena I.; Nevolin, Iurii M.; Egorov, Alexander V.; Saveleva, Elena A.; Kalmykov, Stepan N. (Frontiers in Nuclear Engineering, 2022)
Obtaining reliable thermodynamic sorption data is essential for establishing databases that can be used for the numerial safety evaluations of radioactive waste storage and disposal facilities. For this purpose, new experimental data on the sorption of U(VI), Np(V), and Eu(III) onto synthesized goethite in a wide range of experimental conditions were collected. Thermodynamic surface complexation models based on different approaches were developed and parametrized to fit a large dataset, including experimental data from the current work as well as available literature data. The proposed heuristic optimization procedure allowed identifying and comparing different parametrization variants and their uncertainties for considered models. The developed models pass the test on additional Cd(II) and Zn(II) data, simultaneously providing a reliable description of the sorption process for five cations and could probably be extended using the obtained linear free energy relationship.